2015
DOI: 10.12783/ijast.2015.0301.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixed Urease Inhibitors on N Losses From Surface-applied Urea

Abstract: The effect of mixed urease inhibitors on NH3 volatilization from surface-applied urea was studied. The results showed that mixed urease inhibitors could effectively reduce NH3 volatilization. Mixed urease inhibitors of 0.05% N-(nbutyl)thiophosphoric triamide (NBPT) and 0.05% N-(n-propyl) thiophosphoric triamide (NPPT) reduced NH3 volatilization of23.8% or 28.8% compared with the treatments with single NBPT or NPPT. Mixed inhibitors showed more effectiveness on slowing urea hydrolysis and maintaining lower soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…This is most likely because the combination of two urease inhibitor types would inhibit a broader range of ureases present in the soil. The effects of Limus ® on NH 3 volatilization and N utilization on wheat production in northern China exhibited an 83% reduction in NH 3 losses compared to unprotected urea [70]. The study also found that the application of Limus ® did not significantly affect grain yield [71].…”
Section: N-(n-propyl) Thiophosphoric Triamide (Nppt)mentioning
confidence: 76%
“…This is most likely because the combination of two urease inhibitor types would inhibit a broader range of ureases present in the soil. The effects of Limus ® on NH 3 volatilization and N utilization on wheat production in northern China exhibited an 83% reduction in NH 3 losses compared to unprotected urea [70]. The study also found that the application of Limus ® did not significantly affect grain yield [71].…”
Section: N-(n-propyl) Thiophosphoric Triamide (Nppt)mentioning
confidence: 76%
“…Several urea analogues were shown to more effectively inhibit urea hydrolysis in vitro than NBPT [29] but none of the compounds tested by these authors is commercial so far. A formulation containing NBPT and NPPT (N-(n-propyl) thiophosphoric triamide) has been successfully tested [30] , [31] and has reached the market in the past two years under the brand name Limus. A new urease inhibitor, N-(2-nitrophenyl) phosphoric triamide (2-NPT), was developed in Germany in the early 2000s, has been tested under field conditions [32] and is also reaching the market, which is, so far, amply dominated by NBPT.…”
Section: Introductionmentioning
confidence: 99%
“…Urea is the single most widely used nitrogen (N) fertilizer in the world and accounted for 57% of the global N fertilizer consumption in 2013 and 2014 (Heffer and Prud'homme, 2016). Urea is a desirable N source due to its low cost and high N content (460 g kg –1 ) and is easy for manufacturers and retailers to handle and store (Li et al, 2015). However, the efficiency of urea can be greatly reduced if N is lost from the soil surface through volatilization as ammonia gas.…”
mentioning
confidence: 99%